Retroperitoneal Seminoma in Undescended Testis: A Case Report - Paudel, Sharma; Kayastha, Prakash; Suwal, Sundar; Singh, Shashi Shekhar; Gautam, Bishnu; Chataut, Dinesh (Nepalese Journal of Radiology, 2022)
Testicular seminoma needs to be considered as a differential diagnosis for intra-abdominal mass in the male patient if there is a history of undescended testis. The risk of developing seminoma in an undescended testis is about 4-7.5 times greater than in a normally located testis.The risk of seminoma in undescended testis is increased even after orchidopexy.The identification of the draining gonadal vein can play a key role in the diagnosis of the testicular tumor in undescended intra-abdominally located testis. We report a case of seminoma in the retroperitoneal undescended testis in 50 years old male admitted for abdominal pain and distension